The New Shifting of Community of Practices in Learning Speaking - Resyadilla Azkia; Nasrullah Nasrullah; Emma Rosana Febriyanti (Intensive Journal, 2024)
Speaking is a productive skill that cannot be learned quickly but through a process requiring time, energy, and effort. To accelerate the development of speaking skills, English learners, such as those in senior high school, frequently participate in learning communities, such as Community of Practice. Several studies related to community of practices have been conducted, which reported teacher learning community and learning with peers. However, there is a scarce discussion on the concept of a Community of Practice for learning English-speaking skills. Therefore, this research investigated whether the English Club supports students’ speaking skills. The research methodology used in this study is Narrative Inquiry. The subjects of the research were the students and the coach. The research was conducted at SMA Negeri 6 Banjarmasin. The Researcher employed instruments such as observation checklists and interview guidelines. The findings of the study showed that the English Club at SMA Negeri 6 Banjarmasin supports students in developing their speaking skills. The English Club is a community of students who actively practice using English for communication. The club supports informal learning, focusing on developing public speaking skills through storytelling, speech, and debate. The club's activities are designed to enhance students' fluency and pronunciation.